Viewpoint: What Should We Teach New Software Developers? Why? - Stroustrup, Bjarne (Communications of the ACM, 2010)
The author focuses on what he sees as a disconnect between education in computer science and industrial practice. His view is that computer science must be central to software development. He argues that although companies want computer science graduates to build software, their only experience in software development may have been as hobbyists.